IS THERE A RELATIONSHIP BETWEEN IRRITABLE BOWEL SYNDROME AND GENERALIZED ANXIETY DISORDER? - Afridi, Hamna; Ahmad, Rubina; Sethi, Mifrah Rauf; Irfan, Muhammad (Journal of Postgraduate Medical Institute, 2017)
Objective: To find out the relationship of irritable bowel syndrome (IBS) and generalized anxiety disorder (GAD) among students of Peshawar Medical College and Peshawar Dental College. Methodology: This Cross sectional study was conducted in Peshawar Medical College and Peshawar Dental College from November 2015 to February 2016. ROME III criteria was used for the diagnosis of IBS and to assess GAD, a 7-item Generalized Anxiety Disorder (GAD-7) scale was used. A total of 750 questionnaires were distributed and 604 (80.5%) questionnaires were received back after completion. The data was analyzed using SPSS v.20 and a p value of <0.05 was considered significant. Results: The mean age of the sample was 20.93 ±1.47 years. Majority of the sample comprised of female students (n=387, 64.1%). A total of 223 (36.9%) students met the criteria for IBS and 143 (23.7%) students scored above the cut off for GAD. Eighty-four (13.9%) students that had IBS also had GAD. The correlation of IBS was highly significant with GAD (r=.236, p =.000). Conclusion: More than one third of the medical students were having IBS and a quarter of students were having GAD. More than 20% of students having IBS also had GAD and there was highly significant correlation between IBS and GAD.